Changes in nutritional status (HAZ) of children under five years of age before and during the COVID-19 pandemic in Kuta Malaka, Aceh Besar - Sakina Alvinni; M. Yani; Said Usman (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
The government targets the prevalence of stunting to fall to 14,0%. Kuta Malaka is one of the sub-districts with the highest stunting in Aceh Besar which has priority villages for stunting intervention. The COVID-19 pandemic is expected to affect the nutritional status of children under five due to its impact on the determinants of nutritional status in daily life. This study aimed to determine the nutritional status of toddlers before and during the COVID-19 pandemic in Kuta Malaka, Aceh Besar. Observational analytical research using a cross-sectional design was conducted from November 1 to December 12, 2023. The research sample comprised 185 data points on the nutritional status of children under five years of age obtained from the Community-Based Nutrition Recording and Reporting system (e-PPGBM) of the Kuta Malaka Health Center, which was selected by simple random sampling. Data were analyzed using the Paired T-test and Wilcoxon test at 95% confidence interval (CI). Results: Before the pandemic, 16, 43, and 126 toddlers were severely stunted, stunted, and 126 toddlers were normal. During the pandemic, 4 toddlers were severely stunted, 53 toddlers were stunted, and 128 toddlers were normal. As many as 14 severely stunted toddlers improved to stunted and normal during the pandemic, but there were no significant changes (p= 0,08). In conclusion, there was no significant change in the nutritional status (HAZ) of children under five before and during the COVID-19 pandemic in Kuta Malaka, Aceh Besar.